Pendampingan Gizi dapat Meningkatkan Lingkar Lengan Atas Ibu Hamil KEK di Wilayah Pesisir Kota Kendari - Fatmawati, Fatmawati; Petrus, Petrus; Kristianto, Jusuf; Abadi, Ellyani (Universitas Batanghari Jambi, 2024)
Chronic energy deficiency (CED) is a nutritional problem characterized by an upper arm circumference of â‰¤ 23.5 cm. CED in pregnant women results in pregnancy complications and risks giving birth to babies with low birth weight. Efforts to overcome chronic energy deficiency can be done by providing assistance in the form of education and providing additional food in the form of moringa biscuits on an ongoing basis. Therefore, this research aims to determine the effect of nutritional assistance on the upper arm circumference of pregnant women who experience chronic energy deficiency in the coastal area of Kendari City. This type of research is a quasi experimental design of two groups pre test-post test with control. The sample was pregnant women in the coastal area of Kendari City, consisting of 35 cases and 35 controls. The sampling technique uses purposive sampling. Upper arm circumference data was obtained using an upper arm circumference tape. The results of this study showed that the average upper arm circumference of pregnant women in the intervention group before assistance was 21.19 cm with the smallest size being 21 cm and the largest upper arm circumference being 23 cm and after nutritional assistance the average upper arm circumference was obtained. 23.97 cm. Then in the control group, the average upper arm circumference before nutritional assistance was 26.34 cm and after assistance it was 27.26 cm. The results of the Mann Whitney test obtained a p value of 0.000. The conclusion of this research is that nutritional assistance can increase the upper arm circumference of pregnant women in the coastal areas of Kendari City..